2016
DOI: 10.3746/pnf.2016.21.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Pomegranate Peel Extract against Dietary-Induced Nonalcoholic Fatty Liver in Rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) is caused by fat accumulation and is associated with oxidative stress. In this study, we investigated the potential protective effect of pomegranate (Punica granatum L.) peel extract (PPE) against oxidative stress in the liver of rats with NAFLD. Sprague-Dawley rats were fed a high fat diet (HFD), 20% corn oil, or palm oil for 8 weeks in the presence or absence of PPE. The control group was fed a basal diet. The progression of NAFLD was evaluated histologically and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
1
17
0
6
Order By: Relevance
“…These compounds (elagic acid, punicalagin, punicalin and galagid acid) have been shown to have increased antioxidant and pleiotropic effects and are believed to act in synergy [59,60]. Our findings were found to be similar to studies of Husain et al [61] , Bachoual et al [62] and seem to be compatible with Esmaillzadeh et al [63] as they demonstrated that pomegranate juice significantly reduce the total cholesterol level. The results also go in consistent with Al-Shaaibi et al [64] as they mentioned that administration of Pomegranate peel extract ameliorate liver enzymes, control lipogenesis and improve the histologic image of liver.…”
Section: Discussionsupporting
confidence: 92%
“…These compounds (elagic acid, punicalagin, punicalin and galagid acid) have been shown to have increased antioxidant and pleiotropic effects and are believed to act in synergy [59,60]. Our findings were found to be similar to studies of Husain et al [61] , Bachoual et al [62] and seem to be compatible with Esmaillzadeh et al [63] as they demonstrated that pomegranate juice significantly reduce the total cholesterol level. The results also go in consistent with Al-Shaaibi et al [64] as they mentioned that administration of Pomegranate peel extract ameliorate liver enzymes, control lipogenesis and improve the histologic image of liver.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, SOD enzyme activity was higher in NAFLD group in agreement with previous report using high fat diet [ 58 ]. High concentrations of antioxidant enzymes represent stress oxidation that the body tries to eliminate [ 59 ]. NAFLD increased liver oxidative stress as evidenced by the increase liver's oxidative damage (such as the increase in MDA level) and the inhibition of liver's antioxidant enzymes (CAT) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity and in vivo functionalities of pomegranate extract such as repair and maintenance of hepatic and intestinal function and attenuation of inflammation have been extensively studied [13–20]. Ellagitannins, anthocyanidins, and related polyphenols are thought to be efficient antioxidants extracted from pomegranate ( Punica granatum L.).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of in vitro and in vivo evidence indicates that pomegranate peel extracts possess antioxidant, anticarcinogenic, and anti-inflammatory properties that may be useful in the treatment and prevention of cancer, cardiovascular disease, diabetes, dental conditions, bacterial infections, and ultraviolet-induced skin damage [10–20]. Furthermore, in vivo experiments have shown that pomegranate juice exhibits an inhibitory effect toward age-related diseases such as Alzheimer's disease [21] and Parkinson's disease [22].…”
Section: Introductionmentioning
confidence: 99%